Co-Operative Societies and Poverty Reduction Among Members for Community Development in Rivers State, Nigeria - Adekola, G.; Dokubo, Chidinma (European Scientific Journal, ESJ, 2017)
The paper examined how cooperative societies operating in Rivers State have been carrying out poverty reduction activities among their members so as to help them contribute to community development. The study answered three research questions. The population of this study comprised 2,355 members of twenty one (21) registered cooperative societies whose activities cover thrift and loan, and thrift and credit facilities. Stratified random sampling technique was used to sample 1,103 representing 50% of the members of the twenty one (21) thrift loan and credit cooperative societies which were used for the study. Through the study, authors established that cooperative societies in the area of study have been empowering their members through their poverty reduction activities. However, factors such as Lack of capital and corruption among the heads of cooperative societies in the State have been militating against the effectiveness of the cooperative poverty reduction activities. Therefore, in order to sustain the cooperative poverty reduction activities, cooperators need cooperative education.